1970
DOI: 10.3329/jbau.v7i2.4730
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Resource Use Efficiency of Boro Rice Production

Abstract: This study was attempted to measure and compare resource use efficiency and relative productivity of farming under different tenure conditions in an area of Bhola district. A random sampling technique was used in the study. Sample farmers were classified as owner, crop share tenant and cash tenant farmers. A total of 90 samples, 30 from each class were selected on the basis of random sampling technique. The study explored the difference in the efficiency and productivity among owner, cash tenant and crop share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 2 publications
(2 reference statements)
6
11
0
Order By: Relevance
“…For boro rice production the rumination of the coefficients was 0.808 indicating the production functions exhibit decreasing returns to scale. Almost same result was found by Majumder et al (2009) and reversed result was found by Ahmed et al (2009) for boro rice production.…”
Section: Returns To Scalesupporting
confidence: 75%
See 3 more Smart Citations
“…For boro rice production the rumination of the coefficients was 0.808 indicating the production functions exhibit decreasing returns to scale. Almost same result was found by Majumder et al (2009) and reversed result was found by Ahmed et al (2009) for boro rice production.…”
Section: Returns To Scalesupporting
confidence: 75%
“…The MVP values for all the variables were greater than one which indicated that farmers had chances of increasing per hectare output by utilizing more seedling, urea fertilizers, irrigation and human labour. Majumder et al (2009) reported a similar result for owners and tenant operators, the MVP of seedlings and insecticides were higher than one while for cash tenants MVP of seedlings, insecticides and fertilizers were greater than one. Greater than one MVP ratio to MFC for seed, chemical fertilizers, plant protection chemicals and human labour was also found by Parasar et al (2016).…”
Section: Resource Use Efficiencysupporting
confidence: 65%
See 2 more Smart Citations
“…Again, the BCR in leased land (1.55) of owner cum tenant farmers was higher than this share cropped land (Table 5). The results are in conformity with the findings of Majumder and Roy (2009). 3.6 Impact of socio-economic variables on gross revenues of the share cropped land of owner cum tenant farmers Table 6 presents the summary result of the impact of socio-economic variables on gross revenues.…”
Section: Benefit Cost Ratio (Bcr) Of the Farmerssupporting
confidence: 74%